2013
DOI: 10.1161/atvbaha.113.301360
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Thrombomodulin Gene c.1418C>T Polymorphism With Thrombomodulin Levels and With Venous Thrombosis Risk

Abstract: Objective— To investigate the association of the THBD c.1418C>T polymorphism, which encodes for the replacement of Ala455 by Val in thrombomodulin (TM), with venous thromboembolism (VTE), plasma soluble TM, and activated protein C levels. In addition, human umbilical vein endothelial cells (HUVEC) isolated from 100 umbilical cords were used to analyze the relation between this polymorphism and THBD mRNA and TM protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Because the thrombomodulin gene (THBD) g.1418C>T polymorphism has been associated with the rate of PC activation in cultured HUVECs, 28 we selected passage 2 HUVECs which were homozygous wild type for the THBD g.1418C>T SNP (1418CC). The rate of PC activation increased with the number of H1 alleles, whereas it decreased in the presence of H3.…”
Section: Pc Activation On Huvecsmentioning
confidence: 99%
“…Because the thrombomodulin gene (THBD) g.1418C>T polymorphism has been associated with the rate of PC activation in cultured HUVECs, 28 we selected passage 2 HUVECs which were homozygous wild type for the THBD g.1418C>T SNP (1418CC). The rate of PC activation increased with the number of H1 alleles, whereas it decreased in the presence of H3.…”
Section: Pc Activation On Huvecsmentioning
confidence: 99%
“…A similar association between sTM and age was found earlier. [16] Blood sTM level is determined by hereditary factors [9,13] and by pathological changes that lead to increased proteolytic cleavage of endothelial TM. [17] TM expression is depressed in the aged.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Experimental and clinical studies have shown that a low level of sTM is associated with a prethrombotic state and venous thrombosis. [6][7][8][9] Application of recombinant human sTM is effective in prevention of the venous thrombosis in a rat model and after total hip replacement [10,11] for the treatment of disseminated intravenous coagulation. [12] On the other hand, the increased level of sTM causes severe bleeding after injuries and operations.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies [9,10], there was no statistical significant difference in this allelic variant between DVT patients and controls, which suggests that THBD c.1418C N T might be Recently, a large study assessing the genetic background of Chinese venous thrombosis patients [11] confirmed that the c.1456G N T and c.1418C N T variants had no obvious influence on the occurrence of DVT. A large sample study even suggested that the 1418 T allele might increase the stability of thrombomodulin, which would result in an increased protein C activation rate and a lower risk of venous thrombosis [12]. In addition, Tang et al [11] identified the novel variant THBD c. − 151G N T which was associated with DVT in China.…”
Section: Discussionmentioning
confidence: 99%